Highway maintenance handbook - Atkinson, Ken (Thomas Telford, 1997)
Summary : "In recent years, highway maintenance has become a high profile topic, owning to the greater travel potential of the general public and to the impact of roadworks on commerce following the swing away from rail transport. Highway maintenance was once a low-key activity, but it is now being treated as an important consideration in the overall cost of providing the nations infrastructure. Roads have assumed an increasingly important role in this process, particularly during the past 30 years as a result of the motorway building programme."